ANALISIS PEMDAPATA PETANI PINANG DI KABUPATEN ACEH SELATAN - Siti Raizah; Muhammad Nasir (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2020)
AbstractThe purpose of this study was to analyze how much influence the capital, land area, labor, and fertilizer on the income of areca farmers in District of Aceh Selatan. The data used are polymer data and secondary data, primary data obtained through questionnaires while secondary data are sourced from the Central Statistics Agency (BPS) and the Aceh Agriculture and Plantation Office. This research uses descriptive quantitative research. The data analysis model used in this study is multiple linear regression analysis. The results of the analysis of the coefficient of determination (R2) obtained a value of 0.662 which means that capital, land area, labor, and fertilizer affect areca nut income by 66.2 percent, while the remaining 33.8 percent is influenced by variables outside the model. The results of the simultaneous analysis (f-test) that capital, land area, labor, and fertilizer have a positive and significant effect on the income of areca farmers in District of Aceh Selatan. Suggested to areca farmers so that KUD can be used optimally so that areca nuts can be sold at a higher price compared to the selling price of middlemen so that capital, land area, labor, and fertilizer are used more efficiently.Keywords: Income, Capital, Land Area, Labor,  and Fertilizer